Socio-Legal Analysis of Letter C in Ulayat Land Transactions Among Indigenous Communities - Sukirman; Muammar Alay Idrus; Hairul Maksum (Faculty of Law, University of Mataram, 2025)
Ulayat land transactions based on the Letter C document remain prevalent in many parts of Indonesia, despite lacking explicit recognition in the national land law framework. This article aims to analyze the legality of customary land transactions using Letter C within both customary and national legal perspectives. Employing a socio-legal research method—which combines normative legal analysis with empirical field data collection through interviews and observation—this study examines how legal pluralism shapes the coexistence of state and customary land systems. The findings reveal that Letter C holds strong social legitimacy at the community level due to its historical, administrative, and symbolic functions. Although weak under national law, courts often consider Letter C as supporting evidence in land disputes, consistent with Government Regulation No. 24 of 1997 and Government Regulation No. 18 of 2021, which acknowledge written documents as indicative evidence of land ownership. Transactions are regarded as valid under customary law when they meet the principles of konkret, kontan, and terang, and receive approval from customary leaders and village authorities. In conclusion, while existing recognition remains limited, the future legal framework should explicitly regulate the evidentiary status of Letter C—either as a complementary proof integrated into the national land information system or as a transitional instrument toward formal certification—to reduce agrarian conflicts and strengthen legal protection for indigenous communities.